PENDIDIKAN DAN HUKUM ISLAM DALAM PERSPETIF SEJARAH, SOSIAL DAN POLITIK - Amat, Ali; Salsabila, Mira; Webrizal; Julhadi; Desi Asmaret (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the history, social, and political perspectives of Islamic law and education. The main objective of this research is to examine the sources of Islamic law, including the Qur'an, Hadith, ijma' (consensus), and qiyas (analogy), and their application in different Islamic schools of thought. A qualitative descriptive approach is adopted, employing literature review techniques to gather data from books, articles, and classical and contemporary references on Islamic law. The collected data is analyzed descriptively to provide an in-depth understanding of the concepts of Islamic law and its implementation in societal life. A comparative analysis is also used to examine the application of Islamic law across various schools of thought, such as Hanafi, Maliki, Shafi'i, and Hanbali. The research emphasizes the theoretical discussion on the sources of Islamic law and their role in addressing contemporary issues. Although the scope of this research is limited to the application of Islamic law in certain countries, it provides valuable insights into the dynamics and relevance of Islamic law in facing modern challenges.Keywords: Islamic law, Qur'an, Hadith, ijma', qiyas, Islamic jurisprudence